Development of reporting system for unsafe actions and unsafe conditions - Ahmad Suhaimi, Ahmad Saiful; Zaharudin, Aznifa Mahyam (Universiti Teknologi MARA, Kedah, 2023)
Incidents in the workplace were the result of unsafe actions and unsafe conditions in working environments. It led to injuries or severe damage. In most cases, reports were made after an accident had already taken place. This study focused primarily on pre-accident conditions. The development of the reporting system involved utilizing Kodular in developing a mobile app as the reporting platform. The app integrated with SQL database to securely store and manage the reported data. The self-report was required to be submitted online for any non-occurrence that involved an unsatisfactory condition, behavior, or procedure which did not immediately endanger individuals, but if left uncorrected or repeated in other foreseeable circumstances, would have posed a hazard. Data extracted from the database was visualized in the HazAware Analytics Dashboard, utilizing Microsoft Power BI to present insights through engaging infographics. This research was significant as it established strategies for preventing workplace incidents and raised public awareness.